IgG4 as a Biomarker in Graves’ Orbitopathy - Michał Olejarz; Ewelina Szczepanek-Parulska; Daniela Dadej; Nadia Sawicka-Gutaj; Remigiusz Domin; Marek Ruchała (Mediators of Inflammation)
Immunoglobulin G4-related disease (IgG4-RD) is a chronic inflammatory disorder associated with fibrosis and abundant tissue lymphoplasmacytic infiltrations. It typically affects the pancreas, the salivary glands, and the retroperitoneal space. However, it might also involve multiple other organs, including the orbit and the thyroid. Recent studies have suggested that IgG4 plays a role in the pathophysiology of autoimmune thyroid diseases. This ultimately led to the establishment of new clinical entities called IgG4-related thyroid disease and thyroid disease with an elevation of IgG4. The aim of this paper is to describe the pathophysiological, histopathological, and clinical features of Graves’ Disease (GD) and Graves’ Orbitopathy (GO) with elevated IgG4 levels. Multiple studies have demonstrated higher IgG4 serum concentrations in GD patients than in healthy euthyroid controls. Depending on the studied population, elevated serum IgG4 levels occur in 6.4-23% (average: 10.3%) of all patients with GD, 8.3-37.5% (average: 17.6%) of patients with GO, and 0-9.8% (average: 5.4%) of patients with GD without GO, while GO patients comprise 37.5-100% (average: 65.8%) of all GD patients with elevated IgG4 levels. Characteristic features of GD with elevated IgG4 levels include lower echogenicity of the thyroid gland on ultrasound examination, peripheral blood eosinophilia, higher prevalence of orbitopathy, and better response to antithyroid drugs with a tendency to develop hypothyroidism when compared to patients with GD and normal levels of IgG4. Typical signs of GO accompanied by increased concentration of IgG4 include younger age at diagnosis, and more severe course of the disease with a higher Clinical Activity Score (CAS).. We strongly recommend considering the diagnosis of GO with elevated IgG4 in patients with an established diagnosis of GD, elevated serum IgG4 levels, and clinical features of ophthalmic disease overlapping with those of IgG4-related orbital disease.